Analysis of Financial Performance Measurement at the Jambi City Government Manpower, Cooperatives and SMEs Office Based on the Value For Money Concept - Pratama, Angga; Sam, Iskandar; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2024)
This study aims to evaluate the financial budget performance of the Department of Manpower, Cooperatives, and Small-Medium Enterprises (UKM) of the Jambi City Government through the Value for Money approach. The assessment incorporates three dimensions: economy, efficiency, and effectiveness. Economic value is measured by comparing the actual expenditure to the budgeted cost. Efficiency is calculated using the input-output ratio based on the LAKIP data of the agency, while effectiveness is assessed through the outcome-output ratio. The data analyzed includes activity program budgets for the fiscal years 2017 to 2019.The findings reveal that the budget implementation during the study period was relatively economical, with economic ratios of 94.25% in 2017, 91.71% in 2018, and 94.97% in 2019 indicating that actual expenditures were consistently below budget allocations. The efficiency ratios recorded were 100.55%, 102.07%, and 101.74% for the respective years, suggesting that the programs delivered more output than input, and thus met efficiency criteria. The effectiveness ratio remained stable at 100% across all three years, demonstrating that the output achieved was aligned with the intended outcomes.This study contributes to public sector financial management literature by offering empirical evidence on the applicability of Value for Money principles in evaluating local government budget performance. The results provide practical insights for policymakers and financial managers in enhancing budget accountability and optimizing resource allocation to achieve public service goals effectively and efficiently.